Computer-Controlled Automation of Coffee Bean Drying and Grinding System menggunakan Sensor Infra Red dan Sensor Fototransistor - Syahindra, Wandi; Murlena, Murlena (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to design and implement an automation system for drying and grinding coffee beans using infrared sensors and phototransistors controlled by a computer. Traditional methods are often inefficient and have a high risk of contamination. The automation system, utilizing advanced sensor technology, is expected to improve the efficiency and cleanliness of the coffee bean processing. The research methodology involves designing a system consisting of key components such as infrared sensors to detect moisture, phototransistors to measure light intensity, and actuators driven by stepper motors and DC motors. The research results show that this system can reduce drying and grinding time, improve process accuracy, and decrease manual labor involvement. Simulations and system prototypes demonstrate that this automation system can be practically applied, enhancing the efficiency and cleanliness of the coffee bean processing. In conclusion, this automation system can reduce contamination risk, increase productivity, and lower operational costs in the coffee processing industry.